Worker Protection Standard: What Workers and Handlers Need to Know - Frederick M. Fishel (EDIS, 2006)
Worker employers must make sure that workers have been trained about general pesticide safety (Figure 1). This includes workers who enter treated areas on the farm, forest, nursery, or greenhouse during a restricted-entry interval to perform WPS-permitted tasks. Handler employers must make sure that handlers are trained about general pesticide safety and about correct ways to handle pesticides (Figure 2). This document is PI-114, one of a series of the Pesticide Information Office, UF/IFAS Extension. Original publication date April 2006.